(untitled) (Journal of the Bangladesh Chemical Society, 2013)
Some 5, 7-diaryl-1,5-dihydro (or 1, 2, 3, 5-tetrahydro)- pyrano[2, 3-d] pyrimidin-2, 4- diones (or 2-thioxo-4-ones) (3a-g) has been synthesized in one-step by the cyclocondensation of barbituric acid or thiobarbituric acid (1) with arylideneacetophenones (2a-d), in glacial acetic acid in the presence of phosphorous pentoxide. The structures of the compounds 3a-g were determined by their UV, IR, 1H NMR, 13C NMR, mass spectral data and elemental analyses. Journal of Bangladesh Chemical Society, Vol. 25(2), 124-131, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15064